Creating a Smart Generation: The Role of Education, Family, and Environment in Increasing Reading Interest - Mohammad Nurul Yaqin; Sedya Santosa (CV Projurnal Mitra Publikasi, 2025)
Education plays a central role in shaping character and preparing future generations. One of the fundamental aspects of education is reading, which is not only a means to obtain information, but also to develop critical thinking and broaden horizons. Nonetheless, low interest in reading among adolescents is a major problem that is influenced by various external and internal factors. This research aims to explore the role of education, family and environment in improving reading interest in the younger generation. Using a qualitative approach with a literature study method, this research analyses the various factors that influence students' reading interest and identifies strategies to foster reading interest through more varied education, parental support, and more effective library utilisation. The results show the importance of collaboration between teachers, parents and the environment to create a reading culture that supports the intellectual and character development of the younger generation.